Marriage and parenthood (London : Friends' Book Centre)
1934-11 1934 1930s 22 pages DOUGLAS WHITE. Modern Light on Sex and Marriage. 1933. 3/6. pp.128. Skeffington & Son. A general treatment of the modern outlook on marriage. An excellent introduction to the subject for those who are anxious to gain some insight into present-day problems of sex. * HELENA WRIGHT. The Sex Factor in Marriage. 1930. 3/6. pp.100. Noel Douglas. An excellent guide to a happy, healthy, and mutually satisfactory sex life for both husbands and wives. — — — What is Sex? 1932. 5/-. pp.165. Noel Douglas. A synopsis of sex physiology in plants, animals, and human beings. A most useful outline to put in the hands of young people. All these books, and others, can be borrowed from the Library of the Marriage and Parenthood Committee at Friends House. Books marked * are specially recommended for those desiring a clear, straightforward treatment of the subject without too much detail. (20) 15X/2/478/6